2006
DOI: 10.1073/pnas.0604091103
|View full text |Cite
|
Sign up to set email alerts
|

GEP 100 /BRAG2: Activator of ADP-ribosylation factor 6 for regulation of cell adhesion and actin cytoskeleton via E-cadherin and α-catenin

Abstract: GEP100 (p100) was identified as an ADP-ribosylation factor (ARF) guanine nucleotide-exchange protein (GEP) that partially colocalized with ARF6 in the cell periphery. p100 preferentially accelerated guanosine 5[␥-thio]triphosphate (GTP␥S) binding by ARF6, which participates in protein trafficking near the plasma membrane, including receptor recycling, cell adhesion, and cell migration. Here we report that yeast two-hybrid screening of a human fetal brain cDNA library using p100 as bait revealed specific intera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
57
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(61 citation statements)
references
References 49 publications
4
57
0
Order By: Relevance
“…ARF-GEP100 protein (ADP-ribosylation factorguanine nucleotide-exchange protein-100 kDa) encoded by this gene activates ADP-ribosylation factor protein, ARF6, and regulates cell adhesion through recycling E-cadherin and remodeling actin cytoskeleton. 24 We speculate that these three products might act in the uniform pathway of actin remodeling with ELN/LIMK 25 in smooth Figure 1 The scatter plot of -log 10 P against all the analysis. The four data sets were plotted in -log 10 P of GWAS.…”
Section: Discussionmentioning
confidence: 99%
“…ARF-GEP100 protein (ADP-ribosylation factorguanine nucleotide-exchange protein-100 kDa) encoded by this gene activates ADP-ribosylation factor protein, ARF6, and regulates cell adhesion through recycling E-cadherin and remodeling actin cytoskeleton. 24 We speculate that these three products might act in the uniform pathway of actin remodeling with ELN/LIMK 25 in smooth Figure 1 The scatter plot of -log 10 P against all the analysis. The four data sets were plotted in -log 10 P of GWAS.…”
Section: Discussionmentioning
confidence: 99%
“…Another important function of Arf6 is its role in endosome recycling (36). Recently, several lines of evidence indicated that Arf6 is involved in the membrane trafficking of E-cadherin (37,38). Elucidation of the roles of Arf6 at primordial AJs is needed to understand the molecular mechanisms underlying epithelial polarization.…”
Section: Discussionmentioning
confidence: 99%
“…Brag2 was found to promote the invasive activity of breast cancer cells [34] and myoblast fusion [11,37]. Furthermore, Brag2 was shown to be involved in trafficking processes such as the endocytosis of synaptic AMPA-receptors, E-Cadherin recycling, and phagocytosis of monocytes [21,46,47]. Silencing of Brag2 in HeLa cells increased the surface expression of b1-integrins [15] and a later study indicated that Brag2 might contribute to b1-integrin endocytosis in HeLa cells [33].…”
Section: Introductionmentioning
confidence: 99%